Pengaruh Total Solid dan Perbandingan Bahan Baku dengan Inokulum terhadap Produksi Biogas dari Jerami Jagung - Budiarti, Gita Indah; Shytophyta, Lukhi Mulia; Fajariyanto, Dika; Nugroho, Yusuf Eko (Universitas Ahmad Dahlan, 2018)
The effect of total solid (TS) content and feedstock/inoculum (F/I) ratioÂ on biogas production from corn stover by solidâstate anaerobic digestion (SSâAD) were studied. At a F/I ratio of 2, conversion of corn stover under room temperature resulting in higher biogas yield. SSâAD performed as expected at the TS content of 20%, 22%, 24%. The highest biogas yield of 200 L kgâ1 volatile solids (VS) was obtained at TS content of 22%, F/I ratio of 2.